Uncertainty-aware spot rejection rate as quality metric for proton therapy using a digital tracking calorimeter - Schilling, Alexander; Aehle, Max; Alme, Johan; Barnaföldi, Gergely Gábor; Bodova, Tea; Borshchov, Vyacheslav; Brink, Anthony van den; Eikeland, Viljar; Feofilov, Gregory; Garth, Christoph; Gauger, Nicolas R.; Grøttvik, Ola; et al. (Physics in medicine and biology, 2023)
Objective. Proton therapy is highly sensitive to range uncertainties due to the nature of the dose deposition of charged particles. To ensure treatment quality, range verification methods can be used to verify that the individual spots in a pencil beam scanning treatment fraction match the treatment plan. This study introduces a novel metric for proton therapy quality control based on uncertainties in range verification of individual spots. Approach. We employ uncertainty-aware deep neural networks to predict the Bragg peak depth in an anthropomorphic phantom based on secondary charged particle detection in a silicon pixel telescope designed for proton computed tomography. The subsequently predicted Bragg peak positions, along with their uncertainties, are compared to the treatment plan, rejecting spots which are predicted to be outside the 95% confidence interval. The such-produced spot rejection rate presents a metric for the quality of the treatment fraction. Main results. The introduced spot rejection rate metric is shown to be well-defined for range predictors with well-calibrated uncertainties. Using this method, treatment errors in the form of lateral shifts can be detected down to 1 mm after around 1400 treated spots with spot intensities of 1 × 107 protons. The range verification model used in this metric predicts the Bragg peak depth to a mean absolute error of 1.107 ± 0.015 mm. Significance. Uncertainty-aware machine learning has potential applications in proton therapy quality control. This work presents the foundation for future developments in this area.
Veröffentlicht: 20. September 2023
Gesehen am 15.11.2023